A glow discharge time-of-flight mass spectrometry (GD-TOFMS) study of the 'hydrogen effect' using copper, iron and titanium cathodes. Issue 8 (22nd August 2015) - Mushtaq, Sohail; Steers, Edward B. M.; Whitby, James A.; Horvath, Peter; Michler, Johann; Pickering, Juliet C.
<x xml:space="preserve">Abstract</x> Hydrogen effects are investigated at very low H2 concentrations in an Ar plasma, and the likely discharge mechanisms are discussed.